Embryonic cardiomyocytes can orchestrate various cell protective mechanisms to survive mitochondrial stress. (August 2016) - Magarin, Manuela; Pohl, Toni; Lill, Anette; Schulz, Herbert; Blaschke, Florian; Heuser, Arnd; Thierfelder, Ludwig; Donath, Stefan; Drenckhahn, Jörg-Detlef
Abstract: Whereas adult cardiomyocytes are highly susceptible to stress, cardiomyocytes in the prenatal heart appear to be rather resistant. To investigate how embryonic cardiomyocytes respond to metabolic stress in vivo, we utilized tissue mosaicism for mitochondrial dysfunction in 13.5 dpc mouse hearts. The latter is based on inactivation of the X-linked gene encoding Holocytochrome c synthase ( Hccs ), which is essential for mitochondrial respiration. In heterozygous heart conditional Hccs knockout females ( cHccs +/ − ) random X chromosomal inactivation results in a mosaic of healthy and HCCS deficient cells in the myocardium. Microarray RNA expression analyses identified genes involved in unfolded protein response (UPR) and programmed cell death as differentially expressed in cHccs +/ − versus control embryonic hearts. Activation of the UPR is localized to HCCS deficient cardiomyocytes but does not involve ER stress pathways, suggesting that it is caused by defective mitochondria. Consistently, mitochondrial chaperones, such as HSP10 and HSP60, but not ER chaperones are induced in defective cells. Mitochondrial dysfunction can result in oxidative stress, but no evidence for excessive ROS (reactive oxygen species) production was observed in cHccs +/ − hearts. Instead, the antioxidative proteins SOD2 and PRDX3 are induced, suggesting that ROS detoxification prevents oxidative damage in HCCS deficient cardiomyocytes. Mitochondrial dysfunction and unrestricted UPR can induce cell death, and we detected the initiation of upstream events of both intrinsic as well as extrinsic apoptosis in cHccs +/ − hearts. Cell death is not executed, however, suggesting the activation of antiapoptotic mechanisms. Whereas most apoptosis inhibitors are either unchanged or downregulated in HCCS deficient cardiomyocytes, Bcl-2 and ARC (apoptosis repressor with caspase recruitment domain) are induced. Given that ARC can inhibit both apoptotic pathways as well as necrosis and attenuates UPR, we generated cHccs +/ − embryos on an Arc knockout background ( cHccs +/ −, Arc − / − ). Surprisingly, the absence of ARC does not induce cell death in embryonic or postnatal HCCS deficient cardiomyocytes and adult cHccs +/ −, Arc − / − mice exhibit normal cardiac morphology and function. Taken together, our data demonstrate an impressive plasticity of embryonic cardiomyocytes to respond to metabolic stress, the loss of which might be involved in the high susceptibility of postnatal cardiomyocytes to cell death.